Which features of advanced head and neck basal cell carcinoma are associated with perineural invasion? - Santos,André Bandiera de Oliveira (2017)
Abstract Introduction Perineural invasion is a unique route for tumor dissemination. In basal cell carcinomas, the incidence is low, but increases in advanced cases. Its importance is recognized but not fully understood. Objective To compare head and neck basal cell carcinomas with and without perineural invasion. Methods A retrospective medical chart review of multidisciplinary surgeries for basal cell carcinomas that required a head and neck surgery specialist in a tertiary referral center was performed. Clinical-demographics and histopathological features were analyzed. Results Of 354 cases, perineural invasion was present in 23.1%. Larger tumors and morpheaform subtype were statistically related to perineural invasion. Nodular and superficial subtypes were less frequent in positive cases. No significant difference was found in gender, age, ulceration, location, and mixed histology. Conclusion In this series of selected patients with basal cell carcinomas submitted to major resections, perineural invasion was clearly related to morpheaform subtype and to larger tumors. Other classically associated features, such as location in high-risk mask zone of the face, male gender and mixed histology, were not so strongly linked to perineural invasion.